Концепция фундаментального образования в технических университетах - Чернов И. П. Иван Петрович; Ларионов В. В. Виталий Васильевич; Ерофеева Г. В. Галина Васильевна; Москалев В. А. Владилен Александрович (1994, 1994)
В фонде НТБ ТПУ отсутствует